Determinants of intention to become tax agents among accounting student - Puvaneswari, Veloo (2015)
There is an insufficient number of tax agents in Malaysia. This insufficiency could be due to the intention to become tax agents among accounting students. Theory of Planned Behavior indicates that behavioral intention is the main predictor of actual behavior. Hence, this study attempts to investigate the determinants of factors that could influence the accounting students to become tax agents. In order to determine the intention of accounting students to become tax agents, this study uses the Theory of Planned Behavior as the fundamental theory. The first objective of the study was to determine whether attitude towards becoming tax agents influences the intention to become tax agents among accounting students. The second objective of the study was to determine whether subjective norms influences the intention to become tax agents among accounting students. The last objective was to determine whether perceived behavioral control (self-efficacy and knowledge on tax agent requirements) influences the intention to become tax agents among accounting students. Questionnaire survey were used for data collection. Reliability, validity, descriptive and multiple regression analyses were conducted using the data collected from 330 respondents chosen by using the convenience sampling techniques. The result of multiple regression analyses shows that the independent variables tested can explain 58% variances towards the intention to become tax agents. Hence, the model used in this study were supported being suitable and it was able to predict the dependent variable; intention to become tax agent. From the research findings, it was found that independent variables that influence the intention to become tax agent were attitude, subjective norm and self efficacy